Immune Thrombocytopenia Revealing Enriched IgG-4 Peri-Renal Rosai-Dorfman Disease Successfully Treated with Rituximab: A Case Report and Literature Review. - Razanamahery, Jerome; Humbert, Sebastien; Emile, Jean-Francois; Cohen-Aubart, Fleur; Fontan, Jean; Maksud, Philippe; Audia, Sylvain; Haroche, Julien (Frontiers in Medicine, 2021)
Immune thrombocytopenia (ITP) is a rare autoimmune-mediated condition characterized by isolated thrombocytopenia (<100 G/L) after exclusion of other causes. Mostly primary, it is associated with haematological malignancy, autoimmune disorders, or infection in 20% of patients. It is exceptionally described in patients with histiocytosis, mostly in children (seven patients in literature). We report a case of a 69-year-old man with ITP leading to the diagnosis of histiocytosis. At ITP's diagnosis, the patient had elevated gamma-globulins leading to computed tomography showing bilateral peri-renal infiltration. The biopsy showed enriched IgG4 peri-renal Rosai Dorfman disease with MAP2K1 mutation, although peri-renal infiltration is highly suggestive of Erdheim-Chester disease. This overlapping association was described in men with mutation in MAP2K1 gene. Macrophages are implicated in the pathophysiology of ITP in multiple ways, notably by the phagocytosis of opsonized platelets and their function of antigen-presenting cells able to stimulate autoreactive T cells. Histiocytic cells derivate from monocyte-macrophage lineage. Activation of macrophages in active histiocytosis is responsible for consequential platelet destruction in ITP associated histiocytosis. Finally, this case highlights a rare presentation of ITP revealing histiocytosis, both being efficiently treated with rituximab